Capturing Selfies Motivations and Its Impacts among University Students - Xuc Lin (Jurnal Sinestesia, 2023)
This study attempts to investigate capturing selfies motivation and its impacts among university students. The study used a quantitative approach with a semi-closed questionnaire internet online through Google Forms. The questionnaire was publicly accessible, and WhatsApp and mailing list disseminated an invitation with the link of it. The data collected from May 20-29, 2019. The sample was selected randomly, students aged 17-25 from different universities and different disciplines. There were 316 participants, (28.48%) were male, and (71.25%) were female. Our findings indicate that the frequency of taking selfies of the participants were rarely (46.20%). Most participants (50.63%) preferred taking and posting group selfies. The majority of the participants (66.87%) tend to keep the selfies to themselves rather than posting or sharing it. Most of the participants stated that for archiving, mainly to record the special moment and entertainment, especially to kill boredom as taking and sharing selfies purpose. (46.84%) The participants reported that the satisfaction of taking and sharing selfies is made them understand about how they looked and how people think about them. The majority of the participants (70.57%) felt that selfies have no impact on their daily lives because taking and sharing selfies is not their routine. Most participants believe that recording and archiving memories about their life, experience, and changes are the positive impacts of the selfies. Moreover, the negative of selfies are exposing personal information, and addiction becomes the most concern of the participants.